Which pediatric practices use substance use consultation services? - Levy, Sharon; Ong, Mei-Sing; Minegishi, Machiko; Brogna, Melissa; Mountain-Ray, Shannon; Neubauer, Elyse; Bromberg, Jonas; Straus, John; Weitzman, Elissa R. (Frontiers in Pediatrics, 2024)
Substance use disorders (SUD) are common in adolescents and young adults, though few youth with SUD receive treatment, and rates of medication for substance use disorder treatment are much lower in youth compared to adults. Pediatric primary care could present an opportunity for youth with SUD to access medication, though pediatric providers may need support. Massachusetts has provided a substance use consultation line for pediatric providers since 2018. One large network of independent primary care practices within the state has been further supported by access to resources provided through a grant from the Substance Abuse and Mental Health Services Administration. In this paper, we describe the services provided in Massachusetts and examine whether additional resources are associated with increased use of the consultation line as a marker of provider engagement in SUD treatment.